Calibration of SARRA-H model for climatic risk zoning of cowpea in Eastern Amazon - Paulo J. O. P. Souza; João V. de N. Pinto; Hildo G. G. C. Nunes; Everaldo B. de Souza; Alailson V. Santiago; Gabriel S. T. Fernandes; Matheus L. Rua; Vivian D. da S. Farias; Denis de P. Sousa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to calibrate and test the SARRA-H (Système d’Analyse Régionale des Risques Agroclimatologiques) crop model for cowpea, as well as conducting a climate risk zoning for this crop in a region located in Eastern Amazon, allowing the identification of locations and sowing dates that favor the production considering both the water deficit and the probability of occurrence of severe rains during the harvest period. The model was calibrated and validated with data from experiments conducted between 2013 and 2016 in the municipality of Castanhal, PA, Brazil. Low climate risk areas were defined as those that had a water requirement satisfaction index (WRSI) greater than or equal to 0.5 in the reproductive phase combined with the occurrence of rainfall below 20 mm at the harvest for, at least, 80% of the years for which planting was simulated. The model was able to simulate the water balance, growth and development of cowpea under the climate and soil conditions of the studied location with high precision and accuracy. The optimal period for sowing cowpea comprises the interval between June 5th and 25th for regions located above 2° S and between March 25th and April 15th for regions below 2º S.